Homenaje al profesor Manuel Alvar Ezquerra en Italia - Jaime Peña Arce (Cuadernos AISPI)
Juan Villena Ponsoda; Antonio Ávila Muñoz; Luis Luque Toro (eds.), Homenaje al profesor Manuel Alvar Ezquerra en Italia, Padova, Linea Edizioni, 2024, 374 pp. ISBN 9791281562103